The rise of big government in the United States - Walker, John F. (Sharpe, 1997)
The Rise of Big Government in the United States chronicles the phenomenal growth of local, state, and federal government over the last one hundred years. The authors argue that public and social acceptance (even demand) for government intervention has permitted a strong government role at all levels of the economy. Their argument takes issue with the claim that government has grown by itself and by the bureaucracy's constant push for its own expansion.
Keywords: USA -- Government; Geschichte 1900-2000; Collectieve voorzieningen; Libéralisme économique - États-Unis - Histoire - 20ème siècle; Overheidsuitgaven; Économie mixte - États-Unis - Histoire - 20ème siècle; Außenpolitik; Geschichte; Politik; Wirtschaftspolitik; Fiscal policy -- United States -- History -- 20th century; Free enterprise -- United States -- History -- 20th century; Industrial policy -- United States -- History -- 20th century; Mixed economy -- United States -- History -- 20th century; Bürokratie; Erweiterung; Etats-Unis - Politique économique - 20e siècle; États-Unis - Politique et gouvernement - 20ème siècle; États-Unis - Politique économique - 20ème siècle; États-Unis - Relations extérieures - 20ème siècle; USA; United States -- Economic policy; United States -- Foreign relations -- 20th century; United States -- Politics and government -- 20th century